Physiological and psychological challenges of increasing physical activity and exercise in patients at risk of diabetic foot ulcers: a critical review. Issue 8 (10th June 2016) - Crews, Ryan T.; Schneider, Kristin L.; Yalla, Sai V.; Reeves, Neil D.; Vileikyte, Loretta
Summary: Obesity and a sedentary lifestyle are common challenges among individuals at risk of diabetic foot ulcers. While substantial research exists on physical activity interventions in adults with diabetes, those at greatest risk for foot ulceration were often excluded or not well represented. Both at‐risk patients and their clinicians may be hesitant to increase physical activity because of their perception of diabetic foot ulcer risks. Physical activity is not contraindicated for those at risk of diabetic foot ulcer, yet patients at risk present with unique barriers to initiating increases in physical activity. This review focuses upon the physiological and psychological challenges of increasing physical activity and exercise in patients at risk of diabetic foot ulcers. Offloading, diabetic peripheral neuropathy, depression, pain, self‐efficacy and social support, diabetic foot ulcer risk‐specific beliefs and emotions, and research to date on exercise interventions in this population are all discussed. Additionally, recommendations for implementing and researching physical activity interventions for individuals at risk for diabetic foot ulcer are provided. Copyright © 2016 John Wiley & Sons, Ltd.